Da Remington à redação integrada: a incorporação de tecnologias na prática jornalística e a transformação da visualização da notícia no jornal Zero Hora - Santos, Mariangela Recchia dos (2010)
Considering that technologies used in productives routines contribute to final outcome of journalistic product, this study proposes to identify changes that happened in news visual of newspaper along twenty years, taking the case of Geral section of Zero Hora newspaper. In order to evaluate how the using of digital and printing technologies changed the presentation of the newspaper graphic elements, this dissertation presents a comparative study of elements that constitute the news published in 1989, 1999 and 2009. The study recovers historical data of newspaper and describes the three different phases that editorial room of Zero Hora undergoes, which are analog, computerized and integrated. In theoretical chapter, the impact of technologies in journalistic practices was discussed. The third part of this study is the empirical analysis. It tries to identify how these technologies change the news visual. Among the conclusions appears the fact that the presence of photography decreased in the newspaper, even after the using of digital cameras which made easier to produce and mail a journalistic image. Besides, the size of informative units is decreasing in the last decades in order to give more space to graphic elements, like box and illustrations, and to paratextual elements like cartola. Another conclusion shows that currently more sources were consulted by journalists to write the central news than twenty years ago.